2011
DOI: 10.1038/bjc.2011.254
|View full text |Cite
|
Sign up to set email alerts
|

Circulating sex hormones and breast cancer risk factors in postmenopausal women: reanalysis of 13 studies

Abstract: Background:Breast cancer risk for postmenopausal women is positively associated with circulating concentrations of oestrogens and androgens, but the determinants of these hormones are not well understood.Methods:Cross-sectional analyses of breast cancer risk factors and circulating hormone concentrations in more than 6000 postmenopausal women controls in 13 prospective studies.Results:Concentrations of all hormones were lower in older than younger women, with the largest difference for dehydroepiandrosterone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(145 citation statements)
references
References 71 publications
11
129
1
4
Order By: Relevance
“…Sex hormones that serve essential functions in women's physiology are also known to play a role in the etiology of common diseases such as osteoporosis and bone fractures (1), breast cancer (2,3), and cardiovascular diseases (1). Both experimental and observational studies confirmed the role of estrogens in the etiology of breast cancer (4).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Sex hormones that serve essential functions in women's physiology are also known to play a role in the etiology of common diseases such as osteoporosis and bone fractures (1), breast cancer (2,3), and cardiovascular diseases (1). Both experimental and observational studies confirmed the role of estrogens in the etiology of breast cancer (4).…”
mentioning
confidence: 68%
“…Body weight reflects adipose tissue, which is a source of estrogens and testosterone (50). For smoking, the suggested mechanisms may involve stimulation of hormones synthesis by the adrenal glands (2) through up-regulation of the hypothalamic-pituitary-adrenal axis (3). As for the physical activity, the changes in endogenous sex hormones may be related to modification of body weight (adiposity) (50).…”
Section: Peplonska Et Almentioning
confidence: 99%
“…Although the issue is still not settled, it seems prudent to suggest that the higher prevalence of adverse cardiometabolic risk factors in hyperandrogenic pre-and postmenopausal women does not seem to increase the prevalence of CVD and/or overall mortality (87,89,90,91). After menopause, androgen levels are positively associated with an increased breast cancer risk and other gynecological malignancies (32,92,93,94). The positive correlation of elevated endogenous androgen (testosterone and DHEAS) levels with postmenopausal breast cancer is more evident in estrogen receptor-positive breast tumors (95,96).…”
Section: Sequelsmentioning
confidence: 99%
“…Furthermore, after a woman's reproductive years, various situations related to excess body hair may develop including hirsutism induced by obesity, ovarian hyperthecosis, and androgen-producing tumors (18,20). In addition, the clinical effects of hyperandrogenism alone or within the context of PCOS at this time of life may be related to atherogenesis, insulin resistance, breast cancer, or cardiovascular disease (21,22,23).…”
Section: Introductionmentioning
confidence: 99%